Social innovation for sustainable development: assessing current trends. Issue 4 (19th May 2022) - Leal Filho, Walter; Fritzen, Barbara; Ruiz Vargas, Valeria; Paço, Arminda; Zhang, Qiong; Doni, Federica; Azul, Anabela Marisa; Vasconcelos, Claudio R. P.; Nikolaou, Ioannis E.; Skouloudis, Antonis; Weresa, Marzenna Anna; Marczewska, Magdalena; et al.
ABSTRACT: Innovation is believed to be a key driver of societal and economic well-being. In many cases, it has also led to more sustainable lifestyles and a more efficient use of natural resources. But despite the relevance of innovation as a tool to support sustainable development, there is a need for research that analyses current trends in order to guide future efforts. The present paper addresses this research need. It examines existing methods and tools for fostering social innovation in matters related to sustainable development, within the framework of the SDGs. By means of an online survey undertaken among sustainability and innovation experts in a sample of industrialised and developing nations, this study has identified some of the means via which social innovation is being pursued, along with its applications and limitations. A number of case studies showing examples of sustainable innovation have been mapped to demonstrate its usefulness. A causal loop diagram, which links the factors associated with social innovation within the context of the UN Sustainable Development Goals, is also presented, offering a greater understanding of their interconnections. The paper concludes by outlining some measures that may help to take better advantage of the many opportunities offered by social innovation that put the principles of sustainable development into practice.